Transformasi Saving Society ke Investment Society: Literasi Investasi Digital bagi Ibu Rumah Tangga di Tulungagung - Rendra Erdkhadifa; Badara Shofi Dana; Nadia Nadhirotus Shoidah (Universitas Islam Negeri Imam Bonjol Padang, 2025)
Investment plays an important role in improving the community's economy. In the household, investing is the right step in forming a more mature financial condition in the long term and obtaining passive income. So that awareness to invest needs to be increased, especially for housewives. Housewives take an important role in managing household finances. As a housewife, of course you need extensive knowledge about how to maintain economic stability in the family. The purpose of this community service activity is to provide an understanding to housewives in the neighbourhood unit 02 environment, Tamanan Village, Tulungagung Regency in financial management, understanding of investment, and how to take the right steps in investing. The community service method is community base research, where the approach taken is based on the problem of the target of the community service activity who do not understand the importance of investing in efforts to improve the family economy. The results achieved in the community service activity are that the target of the activity has understood how to control financial management and how to understand the process of investing based on applications. Investasi memiliki peranan penting dalam meningkatkan perekonomian masyarakat. Dalam lingkup rumah tangga, berinvestasi merupakan langkah yang teoat dalam membentuk kondisi keuangan yang lebih matang dalam jangka panjang dan memperoleh pendapatan pasif. Sehingga kesadaran untuk berinvestasi perlu ditingkatkan, khususnya untuk ibu rumah tangga. Ibu rumah tangga mengambil peran penting dalam pengelolaan keuangan rumah tangga. Sebagai ibu rumah tangga, tentu memerlukan pengetahuan yang luas tentang bagaimana menjaga stabilitas ekonomi di dalam keluarga. Tujuan kegiatan pengabdian ini yakni memberikan pemahaman kepada ibu rumah tangga di lingkungan RW.02 kelurahan tamanan kabupaten tulungagung dalam pengelolaan keuangan, pemahaman tentang investasi, dan bagaimana langkah yang tepat dalam berinvestasi. Adapun metode pengabdian yakni community base research, dimana pendekatan yang dilakukan berdasarkan permasalahan sasaran kegiatan pengabdian yang memang belum memahami tentang pentingnya melakukan investasi dalam upaya meningkatkan ekonomi keluarga. Hasil yang dicapai dalam kegiatan pengabdian tersebut, bahwa sasaran kegiatan telah mengerti tentang bagaimana proses dalam melakukan investasi berbasis aplikasi.